PROSES PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA PADA MASA PANDEMI COVID-19 - Khiftiyah, Mariatul; Nilamsari, Wati (Jurnal Pembangunan Manusia, 2022)
The Family Income Improvement Program (UP2K) is a program specifically designed by the government to empower women. This program encourages women to increase their productivity by engaging in entrepreneurship activities. This program aims to empower women to be able to contribute in increasing family income. This study uses a field research method with a qualitative approach. The questions in this study are how the process of empowering women through the UP2K program and how the impact of the implementation of the UP2K program on the lives of the people of RW 01 Pela Mampang Village, Mampang Prapatan District, South Jakarta. The results of this study indicate that the empowerment process through the UP2K RW 01 program is still carried out even during the Covid-19 pandemic. The program implementation process is carried out through home business activities in their respective homes, so that UP2K members can still increase their family income. As for the impact of the UP2K program, there have been changes as evidenced by the increase in income, knowledge, and relations for the implementing members of UP2K RW 01 activities.